The effect of workplace relationship on job satisfaction of employees: School context - BASILIO, GLADYS JEAN; Abun, Damianus (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2023)
The study aimed to examine the workplace relationship between employer and employees and among employees of Divine Word Colleges in the Ilocos Region, Philippines and its effect on job satisfaction. To broaden the understanding of the study, the literature was reviewed, and questionnaires were used to gather data related to workplace relationships and job satisfaction. The respondents of the study are employees of the Divine Word Colleges of Ilocos region which include Ilocos Sur and Ilocos Norte. The study used a descriptive correlational research design. Weighted mean and Pearson r were used to determine the level of workplace relationships and their correlation with job satisfaction. The study found that workplace relations and job satisfaction were good and there is a significant correlation between workplace relationships and job satisfaction.